Revolutionizing Orthopedic Nursing: The Transformative Impact of Artificial Intelligence on Patient Care and Nursing Practices - Priyanka Bansal (International Journal of Orthopedic Nursing and Practices, 2025)
The use of Artificial Intelligence (AI) in orthopedic nursing care has become a game-changer, significantly improving patient care, surgical results, and the efficiency of nursing processes. This review explores the latest trends in AI applications within the field of orthopedic nursing, detailing the scope of these technologies, their impact on patient care, and the challenges faced by healthcare professionals. By examining contemporary literature, this review aims to provide insight into how AI reshapes orthopedic nursing practices and highlights areas requiring further exploration and improvement.
Keywords: Challenges; Patient outcomes; artificial intelligence; healthcare technology; nursing workflow; orthopedic nursing care